A Production and operations management study on Cathay Metal Corporation - Alarcon, Ian Michael (College of Engineering, 2000)
This study was an attempt to apply the concepts and techniques earned from the course, IE 151, to the production system of a company engaged in the fabrication of industrial bars, Cathay Metal Corporation (CAMECO). The group focused their study on rolling mill #3, CAMECO's rolling mill that produces round bars and square bars. Upon documentation of the rolling mill, three major problems were identified by the group through the aid of a Stream Diagnostic Chart. These major problems include: poor inventory management, lack of forecasting technique in use and poor exercise of quality control. The group saw that a tight control over raw material is key to well-managed inventory system. The group thus recommends the use of a billet requirement plan so as to exercise tighter control over raw material, in spite of management?s limited contact with the production unit. The group further saw that though a forecasting technique may not find use in projecting the demand for the product of rolling mill #3 (as they are batch processed), forecasted demands may be extended to project the billet requirements of the rolling mill enabling them plan in advance the procurement of billets (the lot size and time before ordering as determined by the independent demand inventory model, ELS). With the poor exercise of quality control, the group identified three defects recurrent in the rolling mill: misrolls, rerollables and furnace rejects. The group thus suggested that a new system of storing billets be implemented so as to minimize furnace rejects. A more intensive machine check-up schedule was seen to remedy misrolls and rerollables. Lastly, the group recommended a trend fitting technique in considering overhead costs, specifically bunker fuel consumption, so as to optimize the level of production.